dbPepNeo2.0: A Database for Human Tumor Neoantigen Peptides From Mass Spectrometry and TCR Recognition - Lu, Manman; Xu, Linfeng; Jian, Xingxing; Tan, Xiaoxiu; Zhao, Jingjing; Liu, Zhenhao; Zhang, Yu; Liu, Chunyu; Chen, Lanming; Lin, Yong; Xie, Lu (Frontiers in Immunology, 2022)
Neoantigens are widely reported to induce T cell response and lead to tumor regression, indicating a promising potential to immunotherapy. Previously, we constructed an open-access database, i.e. dbPepNeo, to provide a systematic resource for storage and query of the validated neoantigens in cancer researches. In order to expand data volume and application scope, we updated the dbPepNeo to version 2.0 (http://119.3.70.71/dbPepNeo2/home.html). Here, we provide about 801 high confidence (HC) neoantigens (increased by 170%) and 842289 low confidence (LC) HLA peptidomes (increased by 107%). Notably, 55 class Ⅱ HC neoantigens and 630 neoantigen-reactive T cell receptor-β (TCRβ) sequences were firstly included. Besides, two new analytical tools are developed, DeepCNN-Ineo and BLASTdb. DeepCNN-Ineo predicts the immunogenicity of class Ⅰ neoantigens and BLASTdb performs sequence similarity searches against data resources stored in dbPepNeo2.0. Also, the web interface has been greatly refined and enhanced.